KETEPATAN TAKSIRAN BERAT BADAN JANIN DIBANDINGKAN DENGAN BERAT BADAN BAYI BARU LAHIR - Mardeyanti Mardeyanti; Eha Djulaeha; Fatimah Fatimah (Poltekkes Kemenkes Jakarta III, 2013)
Background: Estimated fetal weight of which can be done by measuring the fundus uteri. Estimated fetal weight is of significant importance in the implementation of labor. The accuracy assessment of birth weight, will affect the accuracy of treatment delivery and the results that are expected to reduce mortality and morbidity in childbirth (Cuningham, 2006). Objective: To evaluate the accuracy of estimated fetal weight estimation formula Jonhson Tohsach with birthweight Methods: This study is analytic survey with comparative studies conducted on 153 women who will give birth to aterm pregnancy criteria, pregnant women do not have a disorders (preeclampsia, eclampsia, multiple pregnancy, cesarean). Estimated fetal weight was calculated using the formula Jonhson Tohsach calculation based on fundus height, decrease in the lowest part of the fetus. Results of calculation of estimated fetal weight compared with birth weight. Results: Difference between estimated fetal weight with birth weight is 3077 vs 3132. Statistical tests comparing the average estimated fetal weight with birth weight is not found significant differences with p value 0.0883 (> 0:05). Conclusions: Estimated of fetal weight using the formula Johnson Tohsach high accuracy. need to carefully examine with attention to conduct high-accuracy measurement and uterine fundus examination decreased fetal head